Construction of middle-phase microemulsion system and its micro-mechanism on displacing residual oil in low-permeability porous media - Wu, Tianjiang; Wang, Teng; Hu, Yingxue; Chen, Jiajun; Su, Junwei (Frontiers in Chemistry, 2024)
The application of middle-phase microemulsions in enhancing oil recovery technology represents a significant area of research, particularly for improving production in low-permeability reservoirs. This study utilizes a mixed surfactant system composed of sodium dodecyl benzene sulfonate and coconut oil fatty acid lipopolyoxyethylene betaine at a mass ratio of 1:3, with n-butanol serving as the cosurfactant. The fish phase diagram was instrumental in determining the critical concentration range for alcohol (1.3%-3.7%) necessary for the formation of middle-phase microemulsions, along with a corresponding surfactant mass concentration of 0.3%-0.7%. Key salinity thresholds for middle-phase formation and disappearance were identified at 1.5% and 6.0%, respectively. Optimal solubilization effects were observed at approximately 4.8% NaCl mass concentration, which effectively reduced interfacial tension to 10−3 mN/m. Under specific kinetic conditions, in-situ formation of middle-phase microemulsions occurs as surfactants interact with crude oil within reservoir pores. In comparison to traditional water flooding, middle-phase microemulsions enhance viscosity and create an oil wall at the forefront of displacement. This mechanism facilitates the aggregation and movement of residual oil, which is crucial for enhancing crude oil recovery. Moreover, middle-phase microemulsions exhibit strong solubilization capabilities, making them particularly effective for mobilizing oil in blind-end and unswept areas. The ultra-low interfacial tension achieved between the microemulsion and crude oil promotes the elongation and fragmentation of pore-trapped oil into smaller droplets, ultimately aiding in their displacement and recovery via micro-pore outlets. This unique interaction underscores the potential of middle-phase microemulsion flooding to optimize oil recovery processes, especially in challenging reservoir environments such as those encountered in the Changqing Oilfield formations.